2017
DOI: 10.1080/08982104.2016.1174943
|View full text |Cite
|
Sign up to set email alerts
|

Oral delivery of allopurinol niosomes in treatment of gout in animal model

Abstract: This study reveals that niosomes can be an efficient delivery system for the treatment of gout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…The modified NPs displayed a minor decrease in %EE which could be due to the loss of free drug from the surface of unmodified NPs during conjugation with activated biotin. The formulations exhibited a slow release in the later stage as the polymer erodes slowly at pH 6.8, and the drug is available for dissolution only after the erosion of polymeric layers [39]. Sustained release at a relative pH of a tumour is a desirable characteristic for drug delivery to the tumour as relatively acidic microenvironment has been observed inside tumours which might facilitate site-specific delivery [40].…”
Section: Discussionmentioning
confidence: 99%
“…The modified NPs displayed a minor decrease in %EE which could be due to the loss of free drug from the surface of unmodified NPs during conjugation with activated biotin. The formulations exhibited a slow release in the later stage as the polymer erodes slowly at pH 6.8, and the drug is available for dissolution only after the erosion of polymeric layers [39]. Sustained release at a relative pH of a tumour is a desirable characteristic for drug delivery to the tumour as relatively acidic microenvironment has been observed inside tumours which might facilitate site-specific delivery [40].…”
Section: Discussionmentioning
confidence: 99%
“…In Table 2 , it was observed and concluded that the Higuchi model gave the highest value of the squared correlation coefficient (R2), indicating that this mathematical model was most suitable for describing the release of the NAR from PCL nanoparticles. These results suggest that the release of NAR from PCL nanoparticles is controlled by diffusion [ 37 ]. From these results, the mechanism of the drug release from PCL nanoparticles can be considered to follow the sequence: (1) dissolution media penetrate into polymeric matrix of the nanoparticles through pores; (2) slowly dissolve the drug; and (3) NAR is released by diffusion in the acceptor solution.…”
Section: Resultsmentioning
confidence: 99%
“…It was not possible to obtain histological samples from vasculature of living individuals in this study. While several animal models for gout are available[ 37 - 40 ], most involve injecting MSU crystals within the joints of animals, and to our knowledge, no animal models for vascular urate deposition exist. We have attempted to validate the current approach by scanning ex vivo urinary calculi and in vitro exams of crystalline MSU and calcium with reasonable results (See supplementary material).…”
Section: Discussionmentioning
confidence: 99%